Effect of different floral preservatives on reducing foliage discoloration and increasing vase life of chrysanthemum (Dendranthema × grandiflora) cv White Reagan - JAIN, RITU; JANAKIRAM, T; SINGH, KANWAR PAL; KUMAWAT, G L (The Indian Journal of Agricultural Sciences, 2014)
The experiment was conducted at the Division of Floriculture and Landscaping, Indian Agricultural Research Institute, New Delhi. To enhance the vase life and to reduce the foliage discoloration of chrysanthemum (Dendranthema × grandiflora Ramat.) cv. White Reagan, different floral preservative treatments consisting of cobalt chloride, salicylic acid, sodium nitro prusside, aluminium sulphate, 8- HQC and sucrose were used. Experiment was laid out in completely randomized block design with eleven treatment combinations and each treatment was replicated thrice. It was observed that maximum vase life, solution uptake, increase in flower size and minimum foliage discoloration was observed in flowers held in preservative containing 400 ppm 8-HQC and 1.5% sucrose, which was significantly superior over all other treatments.